The Norms of Epistemology in John Locke’s Philosophy - Hyvien Hiwa Ahmed; Hameed Aziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The subject of epistemology and science itself are two different subjects from each other, despite that, both of them have a direct relationship with human himself. He wants to know about himself, the world around him, events and always analyze problems. This means that man has a desire and a will that drives him to know and explore the world and the universe, and unlike him, none of the other beings will have this will, they only have instincts. In this research, we pose the problem in the form of a question (What are the norms of the subject Knowledge and theory of knowledge for John Locke?). For this purpose, methods of analysis and comparison were used and I tried based on a group of reliable sources in order to arrive at answers to the problems of our research and Key words for our research are: 1- Epistemology 2- Experience – Sense 3- Mind 4- Metaphysical 5- Innate theory Based on his sources accurately, this is what was discussed in the framework of this theory.